2021
DOI: 10.1002/tkm2.1275
|View full text |Cite
|
Sign up to set email alerts
|

Goreisan inhibits vascular endothelial cell migration and angiogenesis

Abstract: Aim Goreisan (GRS) is a Japanese Kampo medicine, which has been clinically used to treat edema and headache. Recently, a clinical study indicated that GRS significantly suppresses the recurrence of chronic subdural hematoma (CSDH). In CSDH, leakage from immature blood vessels on the neomembrane is involved in the recurrence or exacerbation. Although several clinical reports have shown the effectiveness of GRS, the pharmacological properties and underlining mechanism of GRS are not clear. In this study, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It is also worth noting that in the current study, we observed that Goreisan administration to rats for 1 week did not cause a significant change in AQP‐1 protein levels in mesenteric lymphatic vessels. A previous report shows that treatment of human umbilical vein endothelial cells (HUVEC) with 0.1 mg/mL Goreisan for 24 h attenuates VEGF‐induced increases in AQP‐1 mRNA and protein expression 32 . In addition, administration of Goreisan to mice for 1 week decreased angiogenesis in a Matrigel plug assay 32 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also worth noting that in the current study, we observed that Goreisan administration to rats for 1 week did not cause a significant change in AQP‐1 protein levels in mesenteric lymphatic vessels. A previous report shows that treatment of human umbilical vein endothelial cells (HUVEC) with 0.1 mg/mL Goreisan for 24 h attenuates VEGF‐induced increases in AQP‐1 mRNA and protein expression 32 . In addition, administration of Goreisan to mice for 1 week decreased angiogenesis in a Matrigel plug assay 32 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous report shows that treatment of human umbilical vein endothelial cells (HUVEC) with 0.1 mg/mL Goreisan for 24 h attenuates VEGF‐induced increases in AQP‐1 mRNA and protein expression 32 . In addition, administration of Goreisan to mice for 1 week decreased angiogenesis in a Matrigel plug assay 32 . While our results appear to be in contrast to these previous findings, it is difficult to directly compare our in vivo findings to the in vitro findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GRS has both antidiarrhea and tissue-protective effects through inhibiting inflammation-induced AQP3 expression in the intestine [3]. GRS also suppresses angiogenesis by inhibiting migration of endothelial cells and downregulating extracellular signal-regulated kinase (ERK) activation and AQP1 expression, with a preventive effect against chronic subdural hematoma (CSDH) recurrence [4], and reduces the recurrence rate of CSDH [5]. Additionally, GRS has been found to inhibit AQP4 activity and thus has the potential to reduce brain edema after CSDH and other brain injuries [6,7].…”
Section: Introductionmentioning
confidence: 99%